Public Participation in Planning for Community Relocation: A Case Study of Keephills, Alberta - Goldenberg, Sheldon; Frideres, James S.; DiSanto, Joseph E.; Fleising, Usher (Anthropologica, 2022)
When the Provincial Government of Alberta in Western Canada gave a utility company permission to develop and operate a large open pit coal mine, a small rural community in the area was disrupted. Using both survey and ethnographic collection procedures, the authors trace company and community involvement in a public participation program which was implemented by the utility company in 1976, and is still in place a decade later. The results of this study show that while the community and utility company had very different goals, the public participation program implemented by the company averted major outbreaks of conflict. Furthermore, the utility company relocated a small village in the community, built a new school and recreational center, and rebuilt the associated infrastructures at no cost to the community.